Telemetri Flowmeter Menggunakan RF Modul 433MHz - Frima Setyawan Nur Rohman; Ahmadan Ainul Fikri; Ahmad Nur Fuad; Rahmat Rohim; Rifki Firmansyah (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2017)
In the 20th century this distance is still a constraint in efforts to measure and retrieve data. In an efficiency effort, a long distance measuring device is required. One method to measure from a distance is to use the Telemetry method. Telemetry is a method for measuring a variable in which monitoring is done remotely. The use of telemetry can be used to transmit data from the flowmeter sensor to be received by the receiver. This study discusses the effect of obstacles on transmitter work to send data to the receiver and test the accuracy of the flowmeter sensor. From this study it can be concluded that the effective distance of data transmission depends on the obstacle, the farthest distance is the moment without obstacles, then decreases when there is a hitch, and will decrease again when one receiver or transmitter is placed in a closed room. And for the accuracy of the sensor, the percentage of accuracy is low at the time of the slow water current, and vice versa high accuracy is obtained when the water current is fast. Based on the research we poured in this journal, water flow measurements using RF Arduino-based 433MHz Modules can measure the flow of water at a distance of up to 35meter with an average error of only 4.1%.